Potencial de uso da Crotalaria ochroleuca para produção de feno - Ventura , André Christofoleti (2021)
This work aimed to evaluate the potential use of Crotalaria ochroleuca as hay. The adopted treatments have been: spacing between rows at planting (0.25 and 0.50 m) and two residual cutting heights, performed at 82 DAE (0.20 and 0.30 m), with evaluations subdivided in time (40, 54, 68 and 82 days after emergence – DAE) and five repetitions each. The spacing between rows was allocated in the main plots and in the subplots the plant evaluation ages. The variables analyzed have been: plant height, stem diameter, green and dry matter yield. As for chemical characteristics, dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), lignin (LIG), cellulose (CEL), hemicellulose (HEMI) have been evaluated), indigestible protein in neutral detergent (NDIP), indigestible protein in acid detergent (ADIP), in vitro digestibility of organic matter (IVDOM), in vitro dry matter digestibility (IVDMD) and in vitro digestibility of neutral detergent fiber (IVNDFD). The bromatological evaluations have been carried out on plants with different DAE and on hay. There has been an interaction between row spacing and plant age for the stem diameter variable, with the highest values in the 50 cm treatment at 68 and 82 DAE. The greater spacing between rows provided 50% taller plants and increased MF production in the order of 17%. There was no difference in the chemical composition of the hay, as a function of residual heights and spacing between rows, however, the same did not occur in the plants, with a higher DM content (g kg-1), at 40 DAE for the spacing of 0.25m (197 g kg-1) and for the 0.5m spacing the highest average was observed at 82 DAE (195.33 g kg-1). The highest average levels of CP in the plants were observed at 40 DAE (233.49 g kg-1 DM). At other ages, there was no difference between CP contents. The NDF and ADF contents increased with the development of the culture, with the highest values being observed at 82 DAE, with 538.42 and 322.27 g kg-1 of DM for NDF and ADF, respectively. Similarly, the lowest concentrations of LIG, CEL and HEMI were found in the younger harvested plants (40 DAE), which presented, respectively, averages of 145.53; 312.73 and 164.37 g kg-1 MS. Following the phenological stages of the plants, the values of NDIP and ADIP presented their lowest concentrations in the initial phase of development, with values of 229.8 and 297.8 g kg-1of protein, respectively. The IVNDFD showed a reduction according to the growth of the plants, but the lowest average was verified in plants with 68 DAE (470.17 g kg-1of DM). The variables IVDMD and IVDOM did not differ as a function of the different cutting ages of the plants. The spacing between rows did not differ for any of the bromatological variables in plants and hay. Crotalaria ochroleuca proved to be productive even with reduced spacing, and nutritional values were similar to those obtained with larger spacing. The residual cutting height has not influenced the quality of the hay produced from Crotalaria ochroleuca. Plant age directly influenced the quality of forage food, both nutritionally and physically, with considerable changes in protein, fiber and fiber digestibility. Considering the chemical characteristics, the most appropriate to cut C. ochroleuca for making hay is 40 days after emergence.